Introduction to information behaviour - Ford, Nigel (London Facet Publishing, 2015)
"This landmark textbook is an essential primer for students and practitioners interested in information seeking, needs and behaviour, user studies and information literacy. Introduction to Information Behaviour uses a combination of theory and practical context to map out what information behaviour is and what we currently know about it, before addressing how it can be better understood in the future. Nigel Ford argues that new understandings of information behaviour research may help maximise the quality and effectiveness of the way information is presented, sought, discovered, evaluated and used. The book introduces the key concepts, issues and themes of information behaviour, illustrates them using key research studies, and provides a clear path through the complex maze of theories and models. The book is structured to move from the basics to the more complex and employs the pedagogical device of "THINK" boxes which invite the reader to think about concepts as they are introduced in order to consolidate their understanding before moving on. Case studies are included throughout the text and each chapter concludes with a round-up of what has been covered, highlighting the implications for professional information practice."--Back cover.
Includes bibliographical references and index.
Keywords: Information behavior; Information literacy